2016
DOI: 10.4103/1119-3077.197016
|View full text |Cite
|
Sign up to set email alerts
|

The intraoral ultrasonography in dentistry

Abstract: Ultrasonography (USG) is a diagnostic method that the ultrasonic image is created by ultrahigh-frequency sound waves, which have an acoustic frequency above the threshold of human hearing. Compared to other medical imaging methods, USG has several advantages of being real time, portable, inexpensive, radiation free, and noninvasive. In the medicine, most of the USG applications are transcutaneous. However, intraoral USG has been a relatively rare application, it has recently been drawing more interest. Intraor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…The alveolar crest level, the location of cement-enamel junction, and the thickness of alveolar crest were measured from the images and compared favorably with those from the cone-beam computed tomography, with less than a 10% difference. This preliminary and fundamental study reinforced the conclusions from previous studies that ultrasonography has great potential to become a noninvasive diagnostic imaging tool for quantitative assessment of periodontal structures [32,43,44].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The alveolar crest level, the location of cement-enamel junction, and the thickness of alveolar crest were measured from the images and compared favorably with those from the cone-beam computed tomography, with less than a 10% difference. This preliminary and fundamental study reinforced the conclusions from previous studies that ultrasonography has great potential to become a noninvasive diagnostic imaging tool for quantitative assessment of periodontal structures [32,43,44].…”
Section: Discussionsupporting
confidence: 85%
“…The results of a study by Vayron R. et al showed that the ultrasonic response of a dental implant varied significantly as a function of healing time, which paved the way for the development of a new quantitative ultrasound (QUS) method in oral implantology [28][29][30][31]. An important application of this technology can be considered extremely useful for the evaluation of intraosseous lesions, their diagnosis and differential diagnosis, and their follow-up after being treated, while always remembering the absence of ionizing radiation [32,33]. Ultrasonography has been used effectively for the diagnosis of inflammatory lesions, cysts, nonodontogenic and odontogenic tumors, and arteriovenous malformations, and for the differential diagnosis of lesions of endodontic origin.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, metallic dental restorations and beam hardening adjacent to dense cortical bone can reduce the quality of the imaging and its utility 9 . Intraoral ultrasonography (US) is commonly used as a noninvasive initial imaging modality in oral and maxillofacial lesion 10,11 . Intraoral ultrasonography revealed the nature of the lesions, and color Doppler sonography is recommended, as it may identify the predictive factors of cervical lymph node metastasis 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…3 Ultrasonography (USG) is used in dentistry generally for several purposes such as: salivary gland diseases, cervical lymphadenopathy, various soft tissue mass, masticatory, and neck muscles, as well as novel usage areas such as: maxillofacial fractures, periapical lesions, temporomandibular joint, tongue tumors, dental tissue's decay, cracks and fractures, mucosal lesions, periodontal tissues, implant planning, and orthodontic procedures. 8 Compared to other prominent methods of medical imaging, USG has several advantages: it provides images in real-time, is portable, inexpensive, radiation free, non-invasive, and unaffected by metal artifacts, such as dental restorations. [8][9][10][11] It also allows identification of the vascularity via its power Doppler and color Doppler facilities and is capable of differentiating cystic lesions from solid lesions.…”
mentioning
confidence: 99%
“…8 Compared to other prominent methods of medical imaging, USG has several advantages: it provides images in real-time, is portable, inexpensive, radiation free, non-invasive, and unaffected by metal artifacts, such as dental restorations. [8][9][10][11] It also allows identification of the vascularity via its power Doppler and color Doppler facilities and is capable of differentiating cystic lesions from solid lesions. 10,11 The drawbacks of USG include limitations with respect to its field of view, such as physical condition and co-operation of patient, difficulty in imaging structures behind bone and air, and its dependence on a skilled operator.…”
mentioning
confidence: 99%